Autonomous thyroid nodule: Not just a disease of adulthood. - Papadimos, Emily R; Perry, Emily; Goodwin, Bruce; Conwell, Louise S (Journal of Paediatrics & Child Health, 2020)
Paediatric thyroid nodules are more likely to be malignant compared with adults. Differentiated thyroid cancer, including papillary thyroid cancer, which accounts for more than 90% of cases, frequently presents as a thyroid nodule with or without cervical lymphadenopathy. The Bethesda System for Reporting Thyroid Cytopathology is well regarded to categorise thyroid nodules; however, false-negative results, particularly in larger nodules (>4 cm) due to sampling errors can occur.